Hubungan Resiliensi dengan Stres Akademik Selama Pembelajaran Tatap Muka Terbatas Siswa Pada Sekolah Menengah Atas - Ahmad Chandra Jaya; Mirza Irawan (Medan State University, 2022)
The method in this study is a quantitative method with a correlational research design. The purpose of this study was to link resilience with academic stress during limited face-to-face learning for class XI social studies students at SMA N 12 Medan in the 2021/2022 academic year. The population in this study were students in class XI social studies. Sampling in this study used random sampling by taking 25% of all students of class XI IPS SMA N 12 Medan. The sample size is 30 students. Data collection is done by using a questionnaire. The validity of the questionnaire was obtained by using the product moment correlation and the reliability test was obtained by using the Cronbach alpha test. Test the hypothesis using the Pearson product moment formula with the help of SPSS20 for Windows. The results of the analysis showed r = 0.605 and Rsquare = 0.366 and a significance value of 0.000 (p <0.05). Based on these results, a research hypothesis was proposed: